2004
DOI: 10.1021/jp048884m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NO upon N2O Decomposition over Fe/ZSM-5 with Low Iron Loading

Abstract: An Fe/ZSM-5 catalyst with a very high Si/Al ratio was prepared, and using it, the effect of NO upon the kinetics of N2O decomposition was studied. The addition of small, nonstoichiometric amounts of NO was observed to cause the rate to increase by more than an order of magnitude. The kinetics were well-fit by a rate expression that was first order in the partial pressure of N2O for the situation without added NO and separately for the situation where NO was added. The Arrhenius parameters of the rate coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
(87 reference statements)
1
41
0
Order By: Relevance
“…Regarding kinetics and mechanism, either N 2 O dissociation or O 2 desorption have been suggested as the rate determining step in the overall process. [8][9][10][11][12][13][14][15][16][17] From DFT modeling of the…”
Section: Introductionmentioning
confidence: 99%
“…Regarding kinetics and mechanism, either N 2 O dissociation or O 2 desorption have been suggested as the rate determining step in the overall process. [8][9][10][11][12][13][14][15][16][17] From DFT modeling of the…”
Section: Introductionmentioning
confidence: 99%
“…Although extensive experimental and theoretical studies have been devoted to the understanding of the mechanism of the N 2 O decomposition, the nature, the nuclearity, and valence of the active iron sites [3][4][5][6][7]11,12 as well as the rate-limiting step [13][14][15][16][17] are still debated. However, it is generally admitted that whatever the preparation methods, several types of iron are present in Fe-ZSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst activity is known to be sensitive to the presence of other gases in the stream like H 2 O, CO, NO, hydrocarbons, etc. Different research groups have observed that NO accelerates N 2 O decomposition [23][24][25][26][27][28][29]. The activated catalysts lose their activity for the low temperature N 2 O decomposition in the presence of water vapours.…”
Section: Introductionmentioning
confidence: 99%